Factors Affecting Players to Buy Virtual Items in Online Games - Kent Jeshua Perdana; MiharniTjokrosaputro Tjokrosaputro (Graduate Program of Universitas Tarumanagara, 2023)
The fast growth of technology and the internet have ushered in a new era for humanity. One of the advantages of the internet is its entertainment value. Online games are a well-known form of online content. In typical PC or console games, only one or two people play the game on a personal computer. In online games, several players from all over the world to play on game servers over the internet. Playing online games gives gamers a sensation of enjoyment, flow, and satisfaction with the game. These variables will influence the purchase intention of players. This study aimed to explore the influence of flow experience, satisfaction, and enjoyment on purchase intention through the mediation of continuous usage intention. This study is quantitative in nature. The sample for this study consisted of 485 digital gaming participants. The purposive sampling was implemented by distributing online questionnaires that were subsequently analysed with Smart PLS. The findings of this study indicate that the sense of flow, satisfaction, and enjoyment can influence the continuous usage intention. Consequently, flow experience, continuous usage intention, and satisfaction can influence purchase intention. Additionally, enjoyment does not affect purchase intention. Then, flow experience can influence purchase intention directly or through continuous usage intention.